Exports and Labor Demand: Evidence from Egyptian Firm-Level Data - Claudia N. Berg; Raymond Robertson; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2022)
Unlike many countries, Egypt did not experience significant labor market improvements following trade liberalization. In this paper, we build upon the earlier work of Robertson et al. (2021) to investigate why increased Egyptian exports did not directly increase employment. To illustrate the relationship between firm-level exporting and employment, we present a simplified general equilibrium model inspired by Melitz (2003) with two sectors: one able to export and one "reserve" sector. This paper tests the implications of this theory using firm-level data from the World Bank's Enterprise Surveys (ES) in 2013, 2016, and 2020. Our firm-level microanalysis demonstrates that while there is a positive employment response to export expansion, this is not occurring at a large enough scale to be felt at the macro level. To seize the benefits of trade, Egypt requires deeper business environment reforms to incentivize large export, labor-intensive sector growth and integrate its economy into global value chains.
Keywords: F1; C1; 330; exports; trade; employment; labor market; econometrics; Egypt